The Effects of Montelukast on Antioxidant Enzymes and Proinflammatory Cytokines on the Heart, Liver, Lungs, and Kidneys in a Rat Model of Cecal Ligation and Puncture–Induced Sepsis - Ali Kagan Coskun; Murat Yigiter; Akgun Oral; Fehmi Odabasoglu; Zekai Halici; Oner Mentes; Elif Cadirci; Fadime Atalay; Halis Suleyman (The Scientific World Journal)
We investigated the potential protective effects of montelukast (MLK) on cecal ligation and puncture (CLP)–induced tissue injury in vital organs — liver, heart, kidneys, and especially lungs — through inhibition of the proinflammatory cytokine response and the generation of reactive oxygen species (ROS) in rats. The rat groups were (1) a 10-mg/kg MLK-treated CLP group; (2) a 20-mg/kg MLK-treated CLP group; (3) a 20-mg/kg MLK-treated, sham-operated group; (4) a CLP control group; and (5) a sham-operated control group. MLK treatment significantly decreased proinflammatory (tumor necrosis factor-alpha, interleukin-6) cytokine levels following CLP. The lipid peroxide level increased in the lung, heart, liver, and kidney tissues after CLP-induced sepsis, and myeloperoxidase activity increased in the lung, heart, and liver tissues. MLK attenuated this elevation in all tissues except the kidney, dose dependently. The glutathione levels and superoxide dismutase activity were significantly increased in the lung, liver, and kidney tissues after MLK treatment. MLK treatment after CLP also potentially reduced mortality. The lung and kidney tissues were the most protected by MLK under sepsis conditions. We can suggest that MLK reverses the systemic inflammatory reaction to polymicrobial sepsis and thereby reduces multiple organ failure.